The Impact of In-Service EFL Teachers Training Program in The Libyan City of Messalata (Journal of Academic Research, 2024)
This paper explores the impact of English language teacher training programs in the city of Messalata, Libya. This study used a descriptive and quasi-experimental method to answer the raised research questions. Data were collected through questionnaires distributed to English language teachers in the region, whether they were trained or not; and the differences between the two groups in the level of difficulties were measured using the Mann-Whitney U test. Interviews were also conducted with some of the teachers who received the training in addition to the trainer to understand the challenges they faced during and after the training. The study results showed no statistically significant differences between the two groups in most of the areas that the training program addressed except for two aspects: using the Total Physical Response method in teaching and dealing with limited resources. The study also concluded that there are other factors that affect several aspects of the teaching process, such as the educational stage and the gender of the students. In addition, some teachers complained about the generality of the training program and that although it included several aspects of the educational process, it did not guide the teacher on how to deal with the ministry’s curriculum.